ANALYSIS OF THE EDUCATIONAL PROCESS IN TEACHING PHYSICAL AND SPORTS ACTIVITIES COLLECTIVES FOR SECONDARY EDUCATION UNDER THE COMPETENCY APPROACH - Djamal BEKHTAOUI; Djamel MOKRANI (Editura Universităţii din Oradea, 2020)
This study aimed to analysis the educational process in teaching physical and collective sports activities for secondary education in light of the competencies approach, where we used the descriptive analytical approach. The study was conducted on a sample of 206 teachers of physical and sports education working in some high schools in the Algerian region using a questionnaire network. We have come to say that the educational process in teaching collective physical and sports activities is based on educational goals and procedures and evaluation; and through this, the material of physical and sports education becomes a leading role as a result of developing the performance of teachers, and therefore this offering can be considered as a way to reform educational systems through the reform of educational materials.